CD73+ Dendritic Cells in Cascading Th17 Responses of Experimental Autoimmune Uveitis-Induced Mice - Ko, MinHee K.; Shao, Hui; Kaplan, Henry J.; Sun, Deming (Frontiers in Immunology, 2020)
Previous studies have shown that CD73 is pivotal in the conversion of pro-inflammatory adenosine triphosphate into anti-inflammatory adenosine and that immune cells of the same type that express different levels of CD73 are functionally distinct. In this study we show that adenosine enhances the Th17 promoting effect of dendritic cells (DCs), and DCs expressing CD73 critically augment Th17 responses. Bone marrow dendritic cells (BMDCs) do not constantly express CD73; however, a significant portion of the BMDCs expressed CD73 after exposure to Toll-like receptor ligand, leading to stronger Th17 responses by converting adenosine monophosphate to adenosine. We show that the CD73+ BMDCs play a critical role in cascading Th17 responses, and CD73+ BMDCs are functionally augmented after treatment with Toll-like receptor ligand. Splenic antigen presenting cells (DCs) of CD73-/- mouse have a poor Th17-stimulating effect, even after exposure to lipopolysaccharide (LPS) or γδ T cells, indicating that induction of CD73+ DCs is critically involved in augmented Th17 responses. We conclude that CD73+ DCs critically trigger cascading Th17 responses, and the activated Th17 cells that express CD73 further augment Th17 responses, leading to cascading exacerbation. Hence, disabling the CD73 function of DCs should block this cascading response and mitigate Th17 responses.